2020
DOI: 10.1016/j.ijcha.2020.100627
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors and angiotensin-receptor blockers and the risk of COVID-19 infection or severe disease: Systematic review and meta-analysis

Abstract: Objective Animal studies suggested that angiotensin-converting enzyme inhibitors (ACEi) and angiotensin-receptor blockers (ARB) facilitate the inoculation of potentially leading to a higher risk of infection and/or disease severity. We aimed to systematically evaluate the risk of COVID-19 infection and the risk of severe COVID-19 disease associated with previous exposure to (ACEi) and/or ARB). Methods MEDLINE, CENTRAL, PsycINFO, Web of Science Core Collection were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 47 publications
2
49
0
2
Order By: Relevance
“…Administering recombinant soluble ACE‐2 or increasing soluble ACE‐2 in plasma was considered as a therapeutic strategy to inactivate SARS‐CoV‐2 42 . Second, previous retrospective cohort studies 43,44 showed RAAS inhibitors do not increase the susceptibility of COVID‐19 45 . Finally, our meta‐analysis strongly suggested ACEI/ARB treatment was significantly associated with a lower risk of mortality in COVID‐19 infected hypertensive patients.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Administering recombinant soluble ACE‐2 or increasing soluble ACE‐2 in plasma was considered as a therapeutic strategy to inactivate SARS‐CoV‐2 42 . Second, previous retrospective cohort studies 43,44 showed RAAS inhibitors do not increase the susceptibility of COVID‐19 45 . Finally, our meta‐analysis strongly suggested ACEI/ARB treatment was significantly associated with a lower risk of mortality in COVID‐19 infected hypertensive patients.…”
Section: Discussionmentioning
confidence: 72%
“…42 Second, previous retrospective cohort studies 43,44 showed RAAS inhibitors do not increase the susceptibility of COVID-19. 45 Finally, our meta-analysis strongly suggested should shed light on the effects of ACEI/ARB in different populations. Second, the duration of the included study was short.…”
Section: Discussionmentioning
confidence: 86%
“…Our confidence in this finding remains high after incorporating new evidence since the publication of our original review given the consistency of results across studies, representing adults from several geographic regions during different phases of the pandemic. Results are supported by several systematic reviews or meta-analyses ( 92–112 ).…”
Section: Key Question 2: Is Use Of Aceis and Arbs Associated With Mormentioning
confidence: 53%
“…New evidence since the publication of our original review includes results from a randomized controlled trial and 4 large database studies that included patients with a mix of disease severity ( 16–19 , 23 ). These studies consistently found that ACEI or ARB use was not associated with a higher risk for SARS-CoV-2 infection, findings which are further supported by 5 systematic reviews or meta-analyses ( 11 , 14 , 92–94 ). Because we consider these findings to be stable (meaning that future studies are likely to have the same results), we will no longer do literature surveillance on this KQ and will retire it from our living review.…”
Section: Key Question 1: Does the Use Of Aceis And Arbs Before Infectmentioning
confidence: 60%
“…Patoulias et al [ 15 ] showed that, although the use of RASi does not increase the odds for SARS-CoV-2-related death in a global scenario (OR = 1.06, 95% CI 0.77–1.47, I 2 = 83%), it increases the odds for death in Europe by 68% (OR = 1.68, 95% CI 1.05–2.70, I 2 = 82%), while decreasing it in Asia by 38% (OR = 0.62, 95% CI 0.39–0.99, I 2 = 0%). Others have come to the same nonsignificant results in a global perspective, but no subgroup analysis by region was made [ 16 ]. Our study indicates that RASi exposure is not associated with an increase nor decrease in the risk of inhospital all-cause mortality (adjusted OR 0.66, 95% CI 0.31–1.40, p =0.226), even though the odds showed a nonsignificant trend of decrease in the exposed group after adjusting for age and comorbidities (logistic regression coefficient of −0.42) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%